2022
DOI: 10.1039/d2ay01087a
|View full text |Cite
|
Sign up to set email alerts
|

Energy conversion efficiency comparison of different aqueous and semi-aqueous CO2 electroreduction systems

Abstract: An energy conversion efficiency index, that is independent of the anode reaction performance, is proposed for CO2 reduction in aqueous and semi-aqueous systems. The energy conversion efficiency of CO2 reduction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…The overpotentials of �0.3 V, �0.6 V, and �0.9 V are required for Au, Ag, and Cu electrocatalysts, respectively. [28] In contrast, when Pt is used, CO 2 is reduced around the theoretical electrode potential of the CO 2 reduction, and in many cases, it generates CO that strongly adsorbs on the Pt (CO ads ), [29][30][31] which is hard to remove or further reduced in aqueous solutions. [32,33] To transform the activity of Pt catalysts, we previously proposed and succeeded in the CO 2 electroreduction using a Pt-based catalyst in combination with a membrane electrode assembly (MEA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overpotentials of �0.3 V, �0.6 V, and �0.9 V are required for Au, Ag, and Cu electrocatalysts, respectively. [28] In contrast, when Pt is used, CO 2 is reduced around the theoretical electrode potential of the CO 2 reduction, and in many cases, it generates CO that strongly adsorbs on the Pt (CO ads ), [29][30][31] which is hard to remove or further reduced in aqueous solutions. [32,33] To transform the activity of Pt catalysts, we previously proposed and succeeded in the CO 2 electroreduction using a Pt-based catalyst in combination with a membrane electrode assembly (MEA).…”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalysts, such as Au, Ag, Cu, etc., are well known as popular choices for experimental designs due to their CO 2 reduction activity, [3–27] although, these metals require high overpotentials. The overpotentials of ${\ge }$ 0.3 V, ${\ge }$ 0.6 V, and ${\ge }$ 0.9 V are required for Au, Ag, and Cu electrocatalysts, respectively [28] . In contrast, when Pt is used, CO 2 is reduced around the theoretical electrode potential of the CO 2 reduction, and in many cases, it generates CO that strongly adsorbs on the Pt (CO ads ), [29–31] which is hard to remove or further reduced in aqueous solutions [32,33] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CO 2 electrochemical reduction can be performed under ambient conditions, even at the industrial-scale. 3,12,13 In this case, to be competitive, this reaction must retain most of the energy in the final chemical product i.e., high energy conversion efficiency, or low activation energy for CO 2 , 14 and electrochemical (EC) and photoelectrochemical (PEC) approaches have been investigated for CO 2 reduction. 15 This may help produce energy with a lower environmental impact, [16][17][18] as in the case of hydrogen production from water electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is not easy to obtain products by CO 2 electroreduction because experimentally high overpotentials are required to allow the CO 2 -reduction reaction. If the products are CO, HCOOH, and CH 4 , the overpotentials of ∼0.5, ∼1, and ∼1.5 V are known to be necessary, respectively. , This would be attributed to a reaction in which bent CO 2 anion radicals are formed by the first electron transfer to the linear CO 2 . , It has been reported that the required energy can be partially improved by the dynamic limitation of CO 2 molecules in the presence of surrounding hydrated cations and by increasing the specific surface area of the electrocatalyst. …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we have recently succeeded in converting CO 2 into CH 4 with extremely low overpotentials (<0.1 V) by controlling the concentration of the CO 2 gas (to 2–7 vol %) to be fed to the cathode of the MEA containing Pt/C . It was also clarified that the CH 4 -formation reaction proceeds by a Langmuir–Hinshelwood mechanism associated with CO ads and adsorbed H (H ads ) when they are present on the Pt surface in the appropriate molar ratios. , Furthermore, the Faradaic efficiency of the CH 4 generation from the CO 2 reduction successfully increased up to ∼60% without any overpotentials thanks to optimization of the applied electrode potential as well as the electrocatalyst species. The required overpotentials for the CH 4 production by CO 2 reduction have been reported to be ∼0 and ≥1.0 V for Pt and Cu electrocatalysts, respectively . Thus, the Pt electrocatalyst can selectively produce CH 4 from the CO 2 reduction around its thermodynamic equilibrium potential.…”
Section: Introductionmentioning
confidence: 99%